Tính giới hạn \(\lim\limits_{x\to+\infty}\left(\sqrt{1+2x^2}-x\right)\).
\(0\) | |
\(+\infty\) | |
\(\sqrt{2}-1\) | |
\(-\infty\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{2x^3+5x^2-3}{x^2+6x+3}\).
\(-2\) | |
\(+\infty\) | |
\(-\infty\) | |
\(2\) |
Tính giới hạn \(\lim\limits_{x\to+\infty}x\left(\sqrt{4x^2+7x}+2x\right)\).
\(4\) | |
\(-\infty\) | |
\(6\) | |
\(+\infty\) |
Tính giới hạn \(\lim\limits_{x\to+\infty}\left(\sqrt[3]{3x^3-1}+\sqrt{x^2+2}\right)\).
\(\sqrt[3]{3}+1\) | |
\(+\infty\) | |
\(\sqrt[3]{3}-1\) | |
\(-\infty\) |
Tính giới hạn \(\lim\limits_{x\to+\infty}\left(\sqrt{x^2+1}+x\right)\).
\(0\) | |
\(+\infty\) | |
\(\sqrt{2}-1\) | |
\(-\infty\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\left(|x|^3+2x^2+3|x|\right)\).
\(0\) | |
\(+\infty\) | |
\(1\) | |
\(-\infty\) |
Giới hạn \(\lim\limits_{x\to-\infty}\left(x-x^3+1\right)\) bằng
\(1\) | |
\(-\infty\) | |
\(0\) | |
\(+\infty\) |
Giới hạn \(\lim\limits_{x\to+\infty}\left(3^x-5^x\right)\) bằng
\(-1\) | |
\(-\infty\) | |
\(+\infty\) | |
Không tồn tại |
Giới hạn \(\lim\limits_{x\to+\infty}\dfrac{3x^2-4x+1}{-2x^2+x+1}\) bằng
\(-\dfrac{3}{2}\) | |
\(-\dfrac{2}{3}\) | |
\(\dfrac{1}{2}\) | |
\(-\infty\) |
Giới hạn nào sau đây không đúng?
\(\lim\limits_{x\to2018}x=2018\) | |
\(\lim\limits_{x\to+\infty}x^3=+\infty\) | |
\(\lim\limits_{x\to-\infty}x^3=-\infty\) | |
\(\lim\limits_{x\to-\infty}x^3=+\infty\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{\sqrt[3]{x^3+2x^2+1}}{\sqrt{2x^2+1}}\).
\(\dfrac{\sqrt{2}}{2}\) | |
\(0\) | |
\(-\dfrac{\sqrt{2}}{2}\) | |
\(1\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{\sqrt{4x^2-x+1}}{x+1}\).
\(2\) | |
\(-1\) | |
\(-2\) | |
\(+\infty\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{2x-3}{\sqrt{x^2+1}-x}\).
\(-2\) | |
\(+\infty\) | |
\(3\) | |
\(-1\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{2x^3-7x^2+11}{3x^6+2x^5-5}\).
\(-2\) | |
\(+\infty\) | |
\(0\) | |
\(-\infty\) |
Tính giới hạn \(\lim\limits_{x\to-\infty}\dfrac{2x^2+5x-3}{x^2+6x+3}\).
\(-2\) | |
\(+\infty\) | |
\(3\) | |
\(2\) |
Giới hạn \(\lim\limits_{x\to-\infty}\left(\sqrt{x^2+1}-\sqrt{9x^2+2x}\right)\) bằng
\(-2\) | |
\(-\infty\) | |
\(+\infty\) | |
Không tồn tại |
Giới hạn \(\lim\limits_{x\to-\infty}\dfrac{3-2x}{\sqrt{x^2+5}}\) bằng
\(2\) | |
\(-2\) | |
\(+\infty\) | |
\(-\infty\) |
Giới hạn \(\lim\limits_{x\to+\infty}\dfrac{3-2x}{\sqrt{x^2+5}}\) bằng
\(2\) | |
\(-2\) | |
\(+\infty\) | |
\(-\infty\) |
Giới hạn \(\lim\limits_{x\to+\infty}\dfrac{1+3x-2x^2}{x^2+5}\) bằng
\(2\) | |
\(-2\) | |
\(+\infty\) | |
\(-\infty\) |
Giới hạn \(\lim\limits_{x\to1^+}\dfrac{x+3}{x-1}\) bằng
\(-\infty\) | |
\(+\infty\) | |
\(4\) | |
Không tồn tại |